PANDANGAN ISLAM TERHADAP KEPEMIMPINAN PEREMPUAN: KAJIAN FEMINISME ISLAM - Indria Nur; M. Irsya Macap (Pascasarjana IAIN Sorong, 2022)
Women are the most unique creatures. Discourse on the uniqueness of women always attract discussed in various perspectives. Various discourses that emerged about women always actual. One of the unique aspects of women who alwayswarmly discussed was the importance of the role of women in public areas. As well as the Political Parties Law and the Election Law which mandated quota of 30 percent representation of women, both in management and in the competition of political parties into Parliament. Opportunities in the political contest warmed back the conversation between the functions, roles and responsibilities of women in the area of “domestic” with activities in the “public domain”. How can a Muslim should react to it? This research will discuss how womens studies in Qualitative and leadership according to Islamic perspective. So the absence of the crux and the dilemma for Muslim women (Muslimah) in the world take part in the public or politics. Results of the study explained that Islam gives a very high appreciation of women. Al-Qur’an laden with symbols and massages about women. In fact there are two suras that provide specific appreciation of the position and status of women, is surah Al-Nisa and surah Al-Thalaq. Al-Qur’an put women equal to men as caliph and the servant of God in this earth. Differences in the nature of women and men to make women more protected so that they are not abused and that they can fully carry out their duties while maintaining it s dentitiy as a Muslim woman. Thus, in the context of Indonesia, opportunities that are open and public space for opportunities should certainly be welcomed by women, by preparing themselves, not just a figure complementary to men, but as partners and relationships that have reliable quality, because a woman was appointed as the leader due to his ability that has competencies and criteria as leaders expected